Determinants of Human Development Index Using Asy Syatibi’s Maqashid Sharia Approach in North Sumatra Province - Sardini, Syafira; Nasution, Muhammad Lathief Ilhamy; Harahap, Rahmat Daim (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
This study uses Asy-Syatibi’s Maqashid Sharia approach to identify the factors that influence the Human Development Index in North Sumatra Province. This research is quantitative research with the type of time series data in which the data is arranged in a time series. During the observation period from 2013 to 2022, thus the study uses 10 years of observation time. The data analysis technique uses the classical assumption test and multiple linear regression using the Eviews application as its processing. The results of this study indicate that the Hifdzu Nafs and Hifdzu Nasl variables have a significant and positive effect on the Human Development Index in North Sumatra. Meanwhile, the Human Development Index in North Sumatra Province is not affected by Hifdzu’ Aql and Hifdzu Maal.